Biophysical assessment a comparative study of the Das-ay and Pondol Rivers in Hinunangan, Southern Leyte - Anas, Abigail N.
Das-ay River, located in the south of the municipality is known for irrigation to the agricultural lands whereas Pondol River, located in the north end of the municipality is used as drainage in case of excessive rainfall. This study was conducted in February 2022 to assess and compare the physico-chemical parameters as well as the biophysical components of the two rivers in three stream sections (downstream, midstream, and upstream. Rapid river assessment was used for the pgysico-chemical components while fish sample connection was conducting using local means of fishing such as fishing net and hook and line. The physico-chemical parameters of the two rivers were not significantly different from each other except for the salinity and water flow. pH and water flow exhibited a positive correlation, while the temperature, salinity, and water density showed negative correlation. In Das-ay River, Poecilia reticulata was the most abundant species while Eleotris acanthopomus was the most abundant in Pondol River. Poecilia reticulata was also the most widely distributed species, being present in both rivers but mainly dominant in the upstream of Das-ay River. Das-ay River has a species diversity of 1.47 and evenness of 0.16 suggesting that the river is moderately disturbed with a few species dominating the habitat. Pondol river, on the other hand, had a species diversity of 2.22 and evenness of 0.36 meaning that it is slightly disturbed, but the species are more disturbed. The species similarity index of both rivers was at 0.65. This indicates that the rivers have similarities with almost half the species present, This study acts as a baseline information for future monitoring and further conservation of the two rivers in the munipality